2021
DOI: 10.1111/tbed.14182
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes and practices of smallholder farmers on foot and mouth disease control in two Cambodian provinces

Abstract: Food-and-mouth disease (FMD) is endemic in Cambodia. The control programme for FMD has relied on vaccination, with poor vaccination uptake by smallholder farmers becoming an increasing concern. A study to improve the understanding of farmer knowledge, attitudes and practices of FMD control and vaccination was conducted in two Cambodian provinces (Kampong Cham and Pursat). The aim was to identify opportunities to improve the livestock disease control programmes provided by both the government and private sector… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 47 publications
1
7
0
Order By: Relevance
“…Almost similar findings have been reported in other parts of the world such as in Sri Lanka (farmers know clinical signs of FMD between 53% and 78%) and in Kenya (farmers know clinical signs of FMD between 53% and 78%) [11,12]. Others have similarly reported that livestock owners are often aware of the prominent clinical signs of the disease in both their own and neighbouring herds [13,14]. This is especially the case in cattle, where the clinical signs of FMD are more apparent [15,16] than in sheep and goats that show mild or no clinical signs of the disease [17].…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Almost similar findings have been reported in other parts of the world such as in Sri Lanka (farmers know clinical signs of FMD between 53% and 78%) and in Kenya (farmers know clinical signs of FMD between 53% and 78%) [11,12]. Others have similarly reported that livestock owners are often aware of the prominent clinical signs of the disease in both their own and neighbouring herds [13,14]. This is especially the case in cattle, where the clinical signs of FMD are more apparent [15,16] than in sheep and goats that show mild or no clinical signs of the disease [17].…”
Section: Discussionsupporting
confidence: 74%
“…However, it potentially could be a risk factor for the spread of FMDV in endemic regions through releasing the virus into the water or through the mixing of livestock at such locations [39]. In a similar study by Sieng, Patrick [14] it was found that farmers are using various traditional methods to treat their sick cattle such as: using herbs and engine oil aimed to clean lesions and deterring flies, and walking infected cattle through the mud to cauterise the pain arising from lesions.…”
Section: Discussionmentioning
confidence: 99%
“…The Government's focus on widespread delivery of HS vaccination and attempts to improve the position of Cambodia on the OIE-led PCP for FMD is well-known (Blacksell et al, 2019). However, as resources remain restricted to achieve both of these objectives, in-lieu of an Sieng, Patrick, Windsor, et al, 2022). These initiatives are urgently required in Cambodia if the substantial increase in future FMD vaccination rates currently needed is to be achieved.…”
Section: Discussionmentioning
confidence: 99%
“…In Cambodia, a survey of 300 smallholder farmers (January to February 2014) found that FMD outbreaks occurred every year during the study period, with a morbidity rate of over 30% (Sieng, Patrick, Windsor, et al, 2022). Biosecurity and vaccination practices were inadequate, and it was concluded that poor knowledge of disease transmission and biosecurity, with low FMD vaccination coverage and a focus on treatment, contributed to regular FMD outbreaks in these communities.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of disease control, community knowledge, attitudes, and practices play an essential role. For instance, the regular occurrence of the outbreak of foot and mouth disease (FMD) in two Cambodian provinces, Kampong Cham and Pursat, is also affected by poor knowledge of disease transmission and biosecurity, low coverage of FMD vaccination, and focus on treatment [10]. The development of disease risk assessment and mitigation skills must be prioritized, particularly for those in low-resource settings [11,3].…”
Section: Figurementioning
confidence: 99%